(untitled) (Ghana Journal of Science, Technology and Development, 2024)
Young people below age 24 make up about 56.6% of the Ghanaian population among which are adolescents. Teen pregnancy and HIV infections among adolescents are on the rise in the country. In Ghana, sexuality and contraceptive talk are seen as adult talk and are no-go areas for adolescents. Parents who are first educators and custodians of these adolescents refrain from discussions on contraceptives such as condom use and other sexuality matters confronting these sexual groups though studies worldwide show that parents’ have a positive influence on adolescent’s contraceptive decision-making. This paper focused on parents’ perceptions of providing condom education for adolescents. A descriptive cross-sectional quantitative study was employed using an interviewer-administered questionnaire and stratified sampling technique to sample a total of 398 parents from rural and urban communities in the Cape Coast Metropolis. This paper discovered through parents that some adolescents know about condom use and parental contribution to such knowledge was very minimal (5%) because they do not feel comfortable discussing such topics with their adolescent children. Correlation analysis revealed that the higher a parent’s education, the lower the perception that educating adolescents on condom use will have an effect such as initiating them into early sexual experimentation. Given this, the paper recommended that public health education programs should target parents to sensitize them on the essence of communicating and educate their adolescent children on condom use to curb misinformation and misuse about condom usage. This will go a long way to help improve their sexual health now and in adulthood because it is their responsibility. Keywords: Adolescent, Parents’ perception, Condom education, Early sexual experimentation